The Impact of Electronic Customer Relationship Management (E-CRM) Strategy on Customer Loyalty in Mytelkomsel using a Mediation Model - M Irvan; Siti Monalisa (Universitas Islam Indragiri, 2026)
This study investigates the impact of Electronic Customer Relationship Management (E-CRM) strategies, encompassing Functional Dimensions and Personal Dimensions, on Customer Loyalty in the use of the MyTelkomsel application, using Perceived Customer Relationship Quality (comprising cognitive and emotional dimensions) as the mediating construct. Data were collected from 100 MyTelkomsel users through a survey and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results indicate that Functional Dimensions have a positive and significant effect on Perceived Customer Relationship Quality (path coefficient = 0.471) and also exert a positive direct effect on Customer Loyalty (path coefficient = 0.256). Meanwhile, Personal Dimensions positively influence Perceived Customer Relationship Quality (path coefficient = 0.335) but exhibit a negative direct effect on Customer Loyalty (path coefficient = −0.109). Furthermore, Perceived Customer Relationship Quality has a positive and significant effect on Customer Loyalty (path coefficient = 0.539) and serves as a mediator in the relationships between both Functional Dimensions and Personal Dimensions and Customer Loyalty. These findings provide deeper insights into the relationship between E-CRM strategies and customer loyalty in the context of the MyTelkomsel application. They also confirm the mediating role of Perceived Customer Relationship Quality and highlight the strategic value of implementing E-CRM to strengthen customer loyalty in the digital era.